Ultrasonic-assisted synthesis of two dimensional coral-like Pd nanosheets supported on reduced graphene oxide for enhanced electrocatalytic performance - Zelin Cui; Xuefeng Bai (Ultrasonics Sonochemistry, 2021)
Two dimensional (2D) Pd nanosheets supported on reduced graphene oxide (Pd/rGO) were prepared through a sonochemical routine induced by cetyltrimethylammonium bromide (CTAB). Coral-like porous Pd nanosheets (Pd/rGO-u) were obtained under the sonication condition (25 kHz, 600 W, ultrasonic transducer), while square Pd nanosheets (Pd/rGO-c) were produced via traditional chemical reduction. The size of Pd nanosheets of Pd/rGO-u and Pd/rGO-c are 69.7 nm and 59.7 nm, and the thickness are 4.6 nm and 4.4 nm, respectively. The carrier GO was proved to be partially reduced to rGO with good electrical conductivity and oxygen-containing groups facilitated a good dispersion of Pd nanosheets. The interaction between GO and CTAB made the alkyl chain assembles to a 2D lamella micelles which limit the growth of Pd atoms resulting in the formation of 2D nanosheets. A high ultrasonic power promotes the reduction and the formation of porous structure. Additionally, Pd/rGO-u exhibited a favorable electrocatalytic performance toward oxygen reduction reaction (ORR) in alkaline condition, which provided a potential synthetic strategy assisted by sonication for high-performance 2D materials.